Introducción a los estudios de traducción - Aranda, Lucía V. (University Press of America, 2016)
This volume presents key notions of translation studies such as authorship, untranslatable terms, gender issues, paratextuality or invisibility, as well as the role of translation in the colonization and formation of literature. This book draws on a wide variety of examples to provide the reader with an illuminating vision of the history of translation studies around the world.